Psychology of Online Customer Behavior - Meparishvili, Ketevani (Caucasus Journal of Social Sciences, 2016)
The online environment has been dramatically affected by customer behavior over the past years. The challenge of a sophisticated marketer became to outline the factors, which influence customer behavior in order to better plan future marketing objectives. Various dependent and independent factors exist, which are mainly grouped into social and psychological variables. Customers are constantly changing their preferences and behavior through the internet along with technological advance-ments. It became inevitable for a company to outline what the online user experience generates in the minds potential buyers. How the customer goes through the sales tunnel and what leads toward the decision to buy a certain product/service? The aim of this article is to outline the peculiarities of social and psychological factors over the web, which play a key role in internet customer behavior.